IMPROVING STUDENTS’ SPEAKING SKILLS THROUGH THE APPLICATION OF EVERY ONE IS A TEACHER HERE LEARNING STRATEGY - Asriadi Asriadi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research was motivated by the students’ low ability in communication. Considering the small number of students, it seemed appropriate to apply Everyone is a Teacher Here learning strategy so that students became active in learning process, especially in speaking. This research was a classroom action research conducted to sixth grade students at SDN 020 Karya Tani, Kecamatan Kempas. There were 7 students consisting of 2 male students and 5 female students. The instruments used in this research were observation sheets and the speaking ability. The results showed that the average score of the students' speaking ability in cycle I was 69.71% which was in the medium category. Then, in the second cycle, it increased to 82.85% which was in the high category. Based on the research results, it was concluded that Everyone is a Teacher Here learning strategy improved students' speaking skills.